ESTIMATION OF OCEAN HEAT ENERGY POTENTIAL IN INDONESIAN WATERS BASED ON CONVERSION CRITERIA USING CLOSED RANKINE CYCLE - Rafif Latenritatta, Muhammad
The sun is one of the largest sources of energy on planet Earth, and about 70 percent of the earth is ocean. The specific heat capacity of sea water is greater than that of air and land, causing the heat from the sun to remain in the ocean.The final project research aims to estimate the potential of ocean thermal energy in Indonesian waters based on monthly simulation data for 20 years from 2000 to 2020 from a model with a resolution of 0.083° x 0.083° called the Copernicus Marine Environment Monitoring Service (CMEMS). The area under review extends from 9°N – 11°S and 95°E to 141°E and is then focused on the Indonesian Exclusive Economic Zone. This research reviews the reference depth which, according to Nihous (2007),1000 meters is the minimum depth for cold water intake with a value of ?T > 20. The minimum depth for cold water intake in Indonesian waters is found to be in the range of 600 meters, and the consistent depth ranges from 600 meters to 800 meters in the Makassar Strait, the Sulawesi Sea, and the Northern Papua Sea. The power generated at the minimum and consistent depths for cold water intake is 154,91 GW per month, 1858,97 GW per year, and 37.179 GW over 20 years for a depth of 600 meters with a consistent area of 1.044.496 Km2.